Democratising the workplace: worker perspectives on industrial democracy. - Buhlungu, Sakhela (My University, 1994)
The central theme of the transition under way in South Africa is democralisation of all spheres of life. One such sphere is the workplace where millions of workers spend most of their adult lives working for a living. For many years workers and their trade unions have been in the forefront of struggles for better wages and working conditions at the workplace. In many cases these struggles have also been about control at the workplace, or what Goodrich has termed "the demand not to be controlled disagreeably". This paper draws on interviews with workers and shop stewards at two factories in the Transvaal and seeks to establish the extent to which their notion of industrial democracy and worker participation constitutes what Goodrich has called "ii;.: demand to take a hand in controlling". What emerges is not a homogenous understanding of workplace democracy, but a range of views and opinions. The paper also analyses a number of powerful factors which influence or shape the views of workers on the subject of industrial democracy. The conclusion of this discussion is that democracy is part of the consciousness of unionised workers as it is the guiding principle in all union structures. It is therefore inevitable that the demand for democracy at the workplace will become part of organised workers' notion of justice and fairness on the shop floor.
Paper presented at the Wits History Workshop: Democracy, Popular Precedents, Practice and Culture, 13-15 July, 1994.